Comparative effects of low-load blood flow restriction training and high-load resistance training on physical performance in college 800-m runners: a randomized control trial - Yu, Jianhua; Yu, Jingyan; Zhao, Lei; Yang, Yi (Frontiers in Physiology, 2025)
BackgroundHigh-load resistance training (HLRT) is commonly used to enhance performance in 800-m runners but may not always be suitable. Low-load blood flow restriction (BFR) training offers similar benefits to HLRT while reducing these issues. This study aimed to compare the effects of traditional HL-RT and low-load BFR training on muscular strength, power, endurance, and running performance of collegiate 800-m runners over an 8-week training program.MethodsA total of 22 participants were randomly divided into HL-RT group (n = 11) and BFR group (n = 11). Physical performance was assessed at three time points: baseline, mid-intervention, and post-intervention. The tests included the 20-m sprint test (T20m), countermovement jump test (CMJ), smith machine full-squat test (to assess V1 load), plantar flexion rate of force development test (PF-RFD), 200-m test (T200m), and 800-m test (T800m).ResultsSignificant time effects were observed for T20m, CMJ, V1 load, PF-RFD, T200m, and T800m (all P < 0.05), and significant interaction effects between time and group was found for V1load (P < 0.05). Post-training comparisons between the HL-RT and BFR groups revealed a significant improvement in V1 load in the HL-RT group (P < 0.05), while no significant differences were found between the groups for the other performance measures. The present results indicate that both HL-RT and BFR training demonstrate positive effects on the muscular strength, power, endurance, and running performance, while HL-RT demonstrate greater gains in muscular power.ConclusionLow-load BFR training offers an effective alternative to traditional HL-RT for enhancing competitive performance and key physical attributes in collegiate 800-m runners.